The evolution of the anterior capsulotomy - Dorota Wyględowska-Promieńska; Marcin Jaworski; Kamila Kozieł; Richard Packard (Videosurgery and Other Miniinvasive Techniques)
The paper describes the development of the anterior capsulotomy from its early crude beginnings in the 18th century to the possibility of automated surgery today via continuous curvilinear capsulorhexis (CCC). The reasons for the opening of the capsule have changed from a roughly made tear to allow access to the nucleus for its extraction, to the creation of more regular openings to allow support for intraocular lenses. With the development of continuous circular tears it was possible to be certain to contain the intraocular lens (IOL) in the capsular bag. In recent times we have the ability to achieve precision in size and location with lasers and other technologies. This means the capsulotomy can be used to hold the IOL, which will improve the centration of the optic. This is important in premium lenses and should improve predictability of the effective lens position. All of these changes will be highlighted with appropriate illustrations.